Foamed particles and foamed particle molded article
By adding specific hindered amine compounds, inorganic pigments and ultraviolet absorbers to the polypropylene resin, the forming process of foamed particles is optimized, and the problem of difficult to produce a high weathering foamed particle molded body under low forming pressure conditions in the prior art is solved, and excellent in-mold forming and long-term weathering resistance are achieved.
Patent Information
- Application Number
- CN202380061554.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-31
- Filing Date
- 2023-08-18
- Publication Date
- 2025-04-04
AI Technical Summary
The prior art is difficult to produce large-scale foamed particle molded bodies with high weather resistance and excellent physical properties under low forming pressure conditions, especially when exposed to external harsh environments.
The polypropylene resin containing a specific hindered amine compound is used, combined with inorganic pigments and ultraviolet absorbers, and the crystallinity of the polypropylene resin and the content of additives are adjusted, the forming process of foamed particles is optimized to improve their in-mold forming and weather resistance.
It has achieved the manufacture of foamed particle molded bodies with excellent molding properties, long-term weather resistance and good stretch properties under low forming pressure conditions, and is suitable for a variety of application scenarios.
Smart Images

Figure CN119768456A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to expanded particles and expanded particle molded articles. Background Art
[0002] The foamed bead molded body formed by in-mold molding of polypropylene resin foamed beads has excellent chemical resistance, impact resistance, compression strain recovery, etc. Therefore, the polypropylene resin foamed bead molded body is used in a wide range of fields such as food transport containers, packaging or cushioning materials for electrical and electronic components, vehicle parts such as automobile bumpers, building parts such as residential insulation materials, and sundries as impact absorbers, heat insulating materials, and various packaging materials.
[0003] Polypropylene resin foamed particle molded bodies have excellent properties as described above. On the other hand, when the foamed particle molded bodies are used in harsh environments such as long-term exposure to sunlight, there is a risk of resin degradation and reduced physical properties in the foamed particle molded bodies depending on the use environment. Therefore, in order to suppress the degradation of the foamed particle molded bodies, attempts have been made to add weathering agents to improve the weather resistance of the foamed particle molded bodies.
[0004] For example, Patent Document 1 discloses polypropylene resin foam particles containing a hindered amine compound, wherein the heat of fusion of the endothermic peak on the high temperature side of the surface layer and the heat of fusion of the endothermic peak on the high temperature side of the internal foam layer in the DSC curve of the surface layer and the internal foam layer satisfy a specific relationship for the purpose of improving not only the weldability and heat resistance but also the weather resistance.
[0005] In addition, from the viewpoint of reducing the energy required for in-mold molding, the polypropylene resin foamed particles used in the manufacture of the foamed particle molded body are expected to be foamed particles that can obtain a good foamed particle molded body even under low molding pressure conditions. From this viewpoint, polypropylene resins with relatively low crystallinity are sometimes used to manufacture foamed particles.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2003-321567 Summary of the invention
[0009] Technical problem to be solved by the invention
[0010] However, when using a polypropylene resin with low crystallinity, even if a weathering agent is added to improve the weather resistance of the foamed particle molded body, it is difficult to impart long-term weather resistance. In particular, in recent years, there is a demand to use a polypropylene resin foamed particle molded body in applications that are more exposed to the outside. However, when using a polypropylene resin with low crystallinity, it is difficult to obtain a foamed particle molded body that can be used for a long time such as several years to several decades even under harsh conditions.
[0011] In addition, the addition of a weathering agent may reduce the moldability of the expanded beads, and may reduce the tensile strength of the obtained expanded bead molded article. Therefore, it is difficult to obtain expanded beads that have excellent moldability and can produce expanded bead molded articles having high weather resistance and excellent physical properties.
[0012] The technical problem of the present invention is to provide a foamed bead having a polypropylene resin as a base resin, which has excellent in-mold formability and can produce a foamed bead molded body that can maintain a good appearance and good stretching properties for a long time even when used in an environment exposed to the outside.
[0013] Solutions for solving the above technical problems
[0014] The present inventors have discovered that foamed particles containing specific hindered amine compounds can solve the above-mentioned technical problems.
[0015] That is, the present invention is as follows.
[0016] <1> A foamed particle, which is a foamed particle with a polypropylene resin as a base resin and contains a hindered amine compound, wherein the crystallinity of the polypropylene resin is 45% or less, the hindered amine compound has a structure represented by the following formula (I), and the content of the hindered amine compound in the foamed particle is 0.01 mass % or more and 4 mass % or less.
[0017] [Chemistry 1]
[0018]
[0019] (In formula (I), X represents an alkylene group, and Y1 and Y2 each independently represent a hydrocarbon group or a hydrocarbon group bonded via an oxygen atom.)
[0020] <2> The expanded particles according to <1>, further comprising an inorganic pigment, wherein a ratio of a content of the hindered amine compound to a content of the inorganic pigment is 0.01 to 8.
[0021] <3> The expanded beads according to <1> or <2>, further comprising an ultraviolet absorber A having a molecular weight of 360 or more, wherein a content of the ultraviolet absorber A in the expanded beads is 0.01% by mass or more and 2% by mass or less.
[0022] <4> The expanded beads according to any one of <1> to <3>, wherein the hindered amine compound has a molecular weight of 500 to 1000.
[0023] <5> The expanded particles according to any one of <1> to <4>, wherein the bulk density of the expanded particles is 10 kg / m 3 Above 500kg / m 3 the following.
[0024] <6> The expanded beads according to any one of <1> to <5>, wherein the average cell diameter of the expanded beads is 50 μm or more and 250 μm or less.
[0025] <7> An expanded bead molded article obtained by in-mold molding the expanded beads according to any one of <1> to <6>.
[0026] Effects of the Invention
[0027] According to the present invention, it is possible to provide expanded beads having a polypropylene resin as a base resin, which have excellent in-mold moldability and can produce an expanded bead molded body that can maintain a good appearance and good stretching properties for a long time even when used in an environment exposed to the outside. DETAILED DESCRIPTION
[0028] [Foaming particles]
[0029] The foamed particles of the present invention (hereinafter, also referred to as "foamed particles") are foamed particles that use a polypropylene resin as a base resin and contain a hindered amine compound, wherein the polypropylene resin has a crystallinity of 45% or less, the hindered amine compound has a structure represented by the following formula (I), and the content of the hindered amine compound in the foamed particles is 0.01% by mass or more and 4% by mass or less. In addition, the numerical range represented by "to" in this specification means a range that includes the numerical values recorded before and after "to" as the lower limit and the upper limit.
[0030] [Chemistry 1]
[0031]
[0032] (In formula (I), X represents an alkylene group, and Y1 and Y2 each independently represent a hydrocarbon group or a hydrocarbon group bonded via an oxygen atom.)
[0033] <Polypropylene resin>
[0034] The foamed particles use a polypropylene resin as a base resin. In addition, the polypropylene resin in this specification refers to a resin in which the content of structural units derived from propylene in the resin is 50% by mass or more, and the content of structural units derived from propylene in the polypropylene resin is preferably 60% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, and further preferably 85% by mass or more.
[0035] In the present invention, as the polypropylene-based resin, a propylene-based copolymer, a mixture thereof, a mixture of a propylene-based copolymer and a propylene homopolymer, and the like can be used.
[0036] As the propylene copolymer, there can be exemplified a copolymer of propylene and ethylene and / or an α-olefin having a carbon number of 4 to 20. As the α-olefin, there can be exemplified 1-butene, 1-pentene, 1-hexene, 1-octene, 4-methyl-1-butene, etc. In addition, as a copolymer component, the content of the component derived from ethylene and / or the component derived from the α-olefin having a carbon number of 4 to 20 contained in the propylene copolymer is preferably 1 to 15% by mass, more preferably 2 to 12% by mass.
[0037] Among these, polypropylene resin preferably contains as main component the propylene copolymer A containing the component derived from ethylene and / or 1-butene as copolymerization component. As propylene copolymer A, ethylene-propylene copolymer, ethylene-propylene-butylene copolymer etc. can be cited. In addition, in this case, the ratio of the propylene copolymer A in the polypropylene resin is preferably 60 mass % or more, more preferably 80 mass % or more, further preferably 90 mass % or more. In addition, propylene copolymer A is more preferably a propylene random copolymer.
[0038] When the propylene copolymer contains a component derived from ethylene (ethylene component) and / or a component derived from butene (butene component) as a copolymer component, from the viewpoint of further improving the in-mold formability of the foamed particles under low molding pressure conditions, the content of the ethylene component and / or butene component in the propylene copolymer is preferably 1% by mass or more, more preferably 2% by mass or more, and more preferably 3% by mass or more. In addition, from the viewpoint of being able to stably obtain a good foamed particle molded body such as compression strength, the content of the ethylene component and / or butene component in the propylene copolymer is preferably 15% by mass or less, more preferably 12% by mass or less, and more preferably 10% by mass or less. That is, the content of the ethylene component and / or butene component in the propylene copolymer is preferably 1 to 15% by mass, more preferably 2 to 12% by mass, and more preferably 3 to 10% by mass. In addition, the content of the component derived from α-olefin in the polypropylene copolymer can be obtained by IR spectroscopy measurement.
[0039] (Crystallinity)
[0040] The crystallinity of the polypropylene-based resin in the present invention is 45% or less.
[0041] In the past, polypropylene resins with lower crystallinity were sometimes used to manufacture expanded particles from the viewpoint of reducing the energy required for in-mold molding. However, compared with polypropylene resins with higher crystallinity, polypropylene resins with lower crystallinity have lower weather resistance, and even if a weathering agent is added to improve the weather resistance of expanded particle molded bodies, it is sometimes difficult to impart weather resistance. In addition, when using polypropylene resins with lower crystallinity, the in-mold moldability of expanded particles is sometimes reduced due to the addition of a weathering agent, and the tensile strength of the expanded particle molded bodies obtained is sometimes reduced. Therefore, it is difficult to obtain expanded particles that are excellent in in-mold moldability and can manufacture expanded particle molded bodies with high weather resistance and excellent physical properties.
[0042] On the other hand, in the present invention, by using a specific hindered amine compound, even when a polypropylene resin with low crystallinity is used as a base resin and even under a relatively low molding pressure condition, the foamed particles are well fused to each other, and foamed particles that can be used to produce a foamed particle molded body in a relatively wide molding pressure range can be obtained. In addition, a molded body with a good fusion state and long-term weather resistance can be obtained.
[0043] From the viewpoint of improving the in-mold formability of the foamed particles under the condition of low molding pressure, the crystallinity of the polypropylene resin is preferably 42% or less, and more preferably 40% or less. In addition, the lower limit of the crystallinity of the polypropylene resin is approximately 20%, and from the viewpoint of being able to stably obtain a foamed particle molded body with good compression strength, etc., it is preferably 25%, and more preferably 30%. That is, the crystallinity of the polypropylene resin is preferably 20% to 42%, more preferably 25% to 42%, and further preferably 30% to 40%.
[0044] The crystallinity of the polypropylene-based resin is calculated by dividing the heat of fusion of the polypropylene-based resin by the heat of fusion of a complete crystal of polypropylene (207 J / g) (unit: %).
[0045] The heat of fusion of a polypropylene resin can be obtained from a DSC curve obtained by differential scanning calorimetry (DSC) based on JIS K 7122: 1987. Specifically, first, using "(2) a case where a melting temperature is measured after a certain heat treatment" as the state adjustment of the test piece, the test piece is heated from 23°C to 200°C at a heating rate of 10°C / min under a nitrogen inflow rate of 30 mL / min, then maintained at the temperature for 10 minutes, then cooled to 23°C at a cooling rate of 10°C / min, and heated to 200°C again at a heating rate of 10°C / min, thereby obtaining a DSC curve (DSC curve at the time of the second heating). The point at a temperature of 80°C on the obtained DSC curve at the time of the second heating is defined as α, and the point on the DSC curve corresponding to the melting end temperature is defined as β. The heat of fusion of the polypropylene resin can be calculated from the area of the portion surrounded by the DSC curve and the line segment (α-β) in the interval between the points α and β.
[0046] The crystallinity of the polypropylene resin can be adjusted by the type or content of the component derived from α-olefin contained as a copolymer component in the polypropylene resin. For example, the crystallinity of the polypropylene resin can be adjusted to be lower by increasing the content of the α-olefin component in the polypropylene resin.
[0047] (Melting Point)
[0048] From the viewpoint of improving the tensile properties of the expanded bead molded article obtained by in-mold molding of the expanded bead of the present invention, the melting point of the polypropylene resin is preferably 120°C or higher, more preferably 125°C or higher, further preferably 130°C or higher, and further preferably 135°C or higher. On the other hand, from the viewpoint of improving the in-mold moldability of the expanded bead under conditions of low molding pressure, the melting point of the polypropylene resin is preferably 155°C or lower, more preferably 150°C or lower, and further preferably 145°C or lower. That is, the melting point of the polypropylene resin is preferably 120°C to 155°C, more preferably 125°C to 150°C, further preferably 130°C to 145°C, and further preferably 135°C to 145°C.
[0049] A polypropylene resin was used as a test piece, and the melting point of the polypropylene resin was measured based on JIS K 7121: 2012. Specifically, "(2) After a certain heat treatment, the melting temperature was measured" was used as the state adjustment of the test piece. Under the condition of a nitrogen inflow of 30 mL / min, the test piece was heated from 23°C to 200°C at a heating rate of 10°C / min, then kept at this temperature for 10 minutes, then cooled to 23°C at a cooling rate of 10°C / min, and heated to 200°C again at a heating rate of 10°C / min, thereby obtaining a DSC curve (DSC curve at the second heating). Next, the vertex temperature of the melting peak in the DSC curve was calculated, and this value can be used as the melting point of the polypropylene resin. In the case where multiple melting peaks appear in the DSC curve, the vertex temperature of the melting peak with the highest height based on the baseline is used as the melting point.
[0050] (Melt Flow Rate (MFR))
[0051] From the viewpoint of improving the foamability of the resin particles during foaming and the viewpoint of improving the secondary foamability during in-mold molding of the foamed particles, the MFR of the polypropylene resin is preferably 3 g / 10 minutes or more, and more preferably 5 g / 10 minutes or more. In addition, from the viewpoint of more easily and stably suppressing the shrinkage of the foamed particles and more easily suppressing the excessive shrinkage of the molded body during in-mold molding of the foamed particles, the MFR of the polypropylene resin is preferably 10 g / 10 minutes or less, and more preferably 9 g / 10 minutes or less. That is, the MFR of the polypropylene resin is preferably 3 to 10 g / 10 minutes, and more preferably 5 to 9 g / 10 minutes.
[0052] The MFR of the polypropylene-based resin is a value measured under the conditions of a temperature of 230° C. and a load of 2.16 kg in accordance with JIS K 7210-1:2014.
[0053] <Hindered amine compounds>
[0054] The expanded beads in the present invention contain a hindered amine compound from the viewpoint of imparting long-term weather resistance to the obtained expanded bead molded article.
[0055] The hindered amine compound has a structure represented by the following formula (I). One hindered amine compound may be used alone or two or more hindered amine compounds may be used in combination.
[0056] [Chemistry 2]
[0057]
[0058] (In formula (I), X represents an alkylene group, and Y1 and Y2 each independently represent a hydrocarbon group or a hydrocarbon group bonded via an oxygen atom.)
[0059] The hindered amine compound has a 2,2,6,6-tetramethyl-4-piperidinamine moiety in its structure, and therefore can particularly consume free radicals generated by light, inhibiting molecular chain breakage (molecular weight reduction) of the resin caused by oxidation, thereby improving the weather resistance of the resin.
[0060] Furthermore, the hindered amine compound has a structure in which an alkylene group and a 2,2,6,6-tetramethyl-4-piperidinamine moiety are bonded via an ester bond, and thus foamed particles in which cell miniaturization is suppressed can be stably obtained, and the weldability of the foamed particles during in-mold molding can be improved.
[0061] In the above formula (I), the carbon number of the alkylene group represented by X is preferably 1 or more, more preferably 3 or more, further preferably 5 or more, and further preferably 7 or more. In addition, the carbon number of the alkylene group is preferably 20 or less, more preferably 15 or less, further preferably 13 or less, and further preferably 10 or less. That is, from the viewpoint of more easily exerting the effect of the present invention, the carbon number of the alkylene group represented by X in the above formula (I) is preferably 1 to 20, more preferably 3 to 15, further preferably 5 to 13, and further preferably 7 to 10.
[0062] In the above formula (I), Y1 and Y2 each independently represent a hydrocarbon group or a hydrocarbon group bonded via an oxygen atom. From the viewpoint of being able to stably impart relatively long-term weather resistance to the obtained foamed bead molded body, the carbon number of the hydrocarbon groups of Y1 and Y2 is preferably 1 or more, more preferably 3 or more, and further preferably 5 or more. In addition, from the viewpoint of being able to stably improve the weather resistance of the molded body in a relatively short period of time after the molding of the foamed bead molded body, the carbon number of the hydrocarbon groups of Y1 and Y2 is preferably 20 or less, more preferably 16 or less, and further preferably 12 or less. That is, from the viewpoint of being able to more easily exert the effect of the present invention, the carbon number of the hydrocarbon groups of Y1 and Y2 is preferably 1 to 20, more preferably 3 to 16, and further preferably 5 to 12. In addition, the hydrocarbon groups of Y1 and Y2 are preferably alkyl groups.
[0063] Among the hindered amine compounds having a structure represented by the above formula (I), the hindered amine compounds in which Y1 and Y2 are hydrocarbon groups are referred to as NR-type hindered amines. Among the hindered amine compounds having a structure represented by the above formula (I), the hindered amine compounds in which Y1 and Y2 are hydrocarbon groups bonded via oxygen atoms are referred to as NOR-type hindered amines. In addition, among the hindered amine compounds having a structure represented by the above formula (I), the hindered amine compounds in which Y1 and Y2 are hydrogen atoms are referred to as NH-type hindered amines.
[0064] The foamed beads of the present invention contain an NR-type hindered amine or a NOR-type hindered amine having a structure represented by the above formula (I), and therefore have excellent in-mold moldability and can obtain a foamed bead molded article showing high weather resistance for a long period of time. The reason for this is not yet clear, but it can be considered as follows.
[0065] It can be considered that, compared with NH hindered amines, when NR hindered amines or NOR hindered amines having a structure represented by the above formula (I) are added to resin particles for making foamed particles, it is not easy to generate attraction due to interaction with inorganic dispersants such as kaolin, so when the resin particles are foamed, it is easy to suppress the inorganic dispersant in the dispersion medium from adhering to the surface of the resin particles. In addition, it can be considered that the hindered amine compound having a structure represented by the above formula (I) does not have an amino group except for the 2,2,6,6-tetramethyl-4-piperidinamine part, so it is not easy to generate attraction due to interaction with inorganic dispersants such as kaolin, and the inorganic dispersant is difficult to maintain on the surface of the foamed particles. As a result, it can be considered that even if hindered amine compounds are added, it is easy to maintain the weldability of the obtained foamed particles at a high level, so foamed particles with excellent in-mold formability can be obtained.
[0066] Furthermore, it is believed that the NR hindered amine or NOR hindered amine having a structure represented by the above formula (I) is less susceptible to the influence of acidic substances and the like that come into contact with the expanded beads and expanded bead molded articles before obtaining them, and is less likely to be deactivated, compared to the NH hindered amine. Therefore, it is believed that an expanded bead molded article having excellent weather resistance for a long period of time can be obtained.
[0067] From the viewpoint of excellent in-mold formability and being able to more stably obtain a foamed bead molded body showing high weather resistance for a long time, the hindered amine compound preferably contains a NOR hindered amine as a main component. In this case, the proportion of the NOR hindered amine in the hindered amine compound is preferably 60% by mass or more, more preferably 80% by mass or more, and further preferably 90% by mass or more.
[0068] Commercially available hindered amine compounds may be used. Examples of commercially available hindered amine compounds include "Tinuvin 123", "Tinuvin 5100", "Tinuvin 292" and "Tinuvin 765" (all manufactured by BASF).
[0069] (Molecular weight)
[0070] From the viewpoint of suppressing the oozing out of the molded article so that the molded article can stably exhibit long-term weather resistance, the molecular weight of the hindered amine compound is preferably 400 or more, more preferably 500 or more, and even more preferably 600 or more. Furthermore, from the viewpoint of making the hindered amine compound well dispersed in the resin so that the molded article can stably exhibit weather resistance even in a relatively short period of time, the molecular weight of the hindered amine compound is preferably 1000 or less, more preferably 900 or less, and even more preferably 800 or less. That is, the molecular weight of the hindered amine compound is preferably 400 to 1000, more preferably 500 to 900, and even more preferably 600 to 800.
[0071] The molecular weight of the hindered amine compound can be obtained from the atomic weight of the atoms constituting the hindered amine compound. 1 The structure of the NOR hindered amine compound contained in the foamed particles is determined by H-NMR and the molecular weight of the NOR hindered amine compound is determined based on the structure.
[0072] From the viewpoint of making the molded body stably exhibit long-term weather resistance, the content of the hindered amine compound in the foamed particles is 0.01% by mass or more, preferably 0.05% by mass or more, more preferably 0.1% by mass or more, and further preferably 0.2% by mass or more. In addition, from the viewpoint of being able to stably obtain foamed particles with good in-mold moldability and easily obtain a foamed particle molded body with excellent tensile strength, the content of the hindered amine compound in the foamed particles is 4% by mass or less, preferably 3% by mass or less, more preferably 2% by mass or less, and further preferably 1% by mass or less. That is, the content of the hindered amine compound in the foamed particles is preferably 0.05 to 4% by mass, more preferably 0.1 to 3% by mass, more preferably 0.1 to 2% by mass, and further preferably 0.2 to 1% by mass.
[0073] In addition, the foamed particles may also contain hindered amine compounds other than the hindered amine compound having a structure represented by the above formula (I) as long as the effect of the purpose of the present invention is not impaired. On the other hand, from the viewpoint of stably obtaining foamed particles with good in-mold formability, the content of hindered amine compounds other than the hindered amine compound having a structure represented by the above formula (I) in the foamed particles in this case is preferably 40 parts by mass or less, more preferably 30 parts by mass or less, further preferably 20 parts by mass or less, and further preferably 10 parts by mass or less, relative to 100 parts by mass of the hindered amine compound having a structure represented by the above formula (I).
[0074] The content of the hindered amine compound in the expanded particles can be determined, for example, by proton nuclear magnetic resonance (NMR) of the expanded particles.1 H-NMR) measurement. Specifically, the following method can be used. First, freeze-crush the foamed particles and weigh about 2 g. Next, use chloroform as a solvent to perform Soxhlet extraction on the freeze-crushed foamed particles to remove the polymer components and the like that are insoluble in chloroform. Next, mix the chloroform-soluble portion obtained by Soxhlet extraction with acetone, and remove the acetone-insoluble portion. Remove the solvent from the acetone-soluble portion to obtain a solid, use it as a measurement sample, and perform proton nuclear magnetic resonance (H-NMR) analysis. 1 H-NMR) measurement. The content of hindered amine compounds in the measured sample is calculated based on the integrated ratio of the measured hindered amine compound peak to the peak of a standard sample (internal standard sample) with a known concentration, and the content of hindered amine compounds per foamed particle is calculated.
[0075] In addition, as a proton nuclear magnetic resonance ( 1 H-NMR), for example, AL-400 manufactured by JEOL Ltd. can be used. In addition, the following measurement conditions can be adopted: solvent: CDCl 3 , internal standard sample: tetrachloroethane (TCE).
[0076] <Pigment>
[0077] From the viewpoint of providing a molded article with a good appearance, the expanded particles of the present invention preferably further contain a pigment. The pigment may be either an inorganic pigment or an organic pigment, but is preferably an inorganic pigment.
[0078] Examples of the organic pigment include azo pigments, diazo pigments, phthalocyanine pigments, quinacridone pigments, isoindolinone pigments, dioxazine pigments, perylene pigments, perinone pigments, thioindigo pigments, anthraquinone pigments and quinophthalone pigments.
[0079] As inorganic pigments, for example, black inorganic substances such as carbon black, carbon nanotubes, graphene, iron black, titanium black, etc. can be cited; white inorganic substances such as titanium dioxide, zinc oxide, silicon dioxide, aluminum oxide, magnesium oxide, antimony trioxide, barium sulfate, and zinc lithopone, etc.; red inorganic substances such as iron oxide red; yellow inorganic substances such as iron yellow and zinc yellow; green inorganic substances such as chrome green and cobalt green; blue inorganic substances such as ultramarine blue, Prussian blue, cobalt blue, and YInMn (yttrium indium manganese) blue, etc. In addition, in this specification, pigment refers to a substance that has the effect of giving color to the foamed particles or the foamed particle molded body and the effect of toning the foamed particles or the foamed particle molded body by being present in the resin component constituting the foamed particles. In addition, the pigment contained in the foamed particles refers to the pigment present in the resin component constituting the foamed particles.
[0080] From the viewpoint of being able to impart a good black appearance, the inorganic pigment preferably contains carbon black and / or titanium oxide. In addition, when the inorganic pigment contains carbon black, the proportion of carbon black in the inorganic pigment is preferably 50% by mass or more, more preferably 60% by mass or more, further preferably 80% by mass or more, and further preferably 90% by mass or more.
[0081] As carbon black, for example, channel black, roll black, furnace black, thermal black, acetylene black, etc. can be used.
[0082] In the case where the expanded particles contain inorganic pigments, from the viewpoint of suppressing the generation of color unevenness in the molded body and easily obtaining a molded body with a good appearance, the content of the inorganic pigment in the expanded particles is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, further preferably 0.1% by mass or more, further preferably 1% by mass or more, and further preferably 2% by mass or more. In addition, from the viewpoint of stably obtaining expanded particles with good in-mold formability, the content of the inorganic pigment in the expanded particles is preferably 10% by mass or less, more preferably 8% by mass or less, further preferably 5% by mass or less, and further preferably 4% by mass or less. That is, the content of the inorganic pigment in the expanded particles is preferably 0.01 to 10% by mass, more preferably 0.05 to 8% by mass, further preferably 0.1 to 5% by mass, further preferably 1 to 4% by mass, and further preferably 2 to 4% by mass.
[0083] In addition, in the past, when inorganic pigments were added to the foamed particles in order to give the foamed particle molded body a color, there was a tendency for the in-mold moldability of the foamed particles to decrease. On the other hand, in the present invention, by using a specific hindered amine compound, even when inorganic pigments were added to the foamed particles, the foamed particles were well fused to each other even under relatively low molding pressure conditions, and foamed particles that can be used to manufacture foamed particle molded bodies within a relatively wide molding pressure range can be obtained. In addition, a molded body with a good fusion state and long-term weather resistance can be obtained.
[0084] (Hindered amine compound content / inorganic pigment content)
[0085] In the case where the expanded particles contain an inorganic pigment, from the viewpoint of stably obtaining expanded particles capable of producing an expanded particle molded body exhibiting good weather resistance for a long period of time, the ratio of the content of the hindered amine compound in the expanded particles to the content of the inorganic pigment is preferably 0.01 or more, more preferably 0.02 or more, further preferably 0.04 or more, and further preferably 0.05 or more. In addition, from the viewpoint of stably obtaining expanded particles having good weldability and good in-mold moldability, the ratio of the content of the hindered amine compound in the expanded particles to the content of the inorganic pigment is preferably 10 or less, more preferably 8 or less, further preferably 6 or less, and further preferably 3 or less. That is, the ratio of the content of the hindered amine compound in the expanded particles to the content of the inorganic pigment is preferably 0.01 to 10, more preferably 0.02 to 8, further preferably 0.04 to 6, and further preferably 0.05 to 3.
[0086] <Ultraviolet light absorber>
[0087] From the viewpoint of improving the weather resistance of the molded article, the expanded particles of the present invention preferably contain an ultraviolet absorber. The ultraviolet absorber preferably contains an ultraviolet absorber A having a molecular weight of 360 or more.
[0088] The ultraviolet absorber is a compound having the property of absorbing ultraviolet rays, and refers to a compound that mainly absorbs light with a wavelength of 280nm to 400nm and converts the absorbed energy into energy such as heat, thereby being able to suppress the degradation of the resin caused by ultraviolet rays. Among the ultraviolet absorbers used for polypropylene resins, there are benzophenone compounds such as benzophenone derivatives (benzophenone ultraviolet absorbers), benzotriazole compounds such as benzotriazole derivatives (benzotriazole ultraviolet absorbers), triazine ultraviolet absorbers such as triazine derivatives (triazine ultraviolet absorbers), benzoate compounds such as benzoate or its derivatives (benzoate ultraviolet absorbers), etc.
[0089] (Molecular weight)
[0090] From the viewpoint of imparting long-term and more excellent weather resistance to the foamed bead molded article, the molecular weight of the ultraviolet absorber A is preferably 300 or more, more preferably 360 or more, further preferably 380 or more, and further preferably 400 or more. In addition, the upper limit of the molecular weight of the ultraviolet absorber A is not particularly limited as long as it is within the range that can achieve the intended purpose of the present invention, but from the viewpoint that the ultraviolet absorber can be efficiently added to the polypropylene resin and the weather resistance of the obtained foamed bead molded article can be stably improved, it is preferably 600, and more preferably 550. That is, the molecular weight of the ultraviolet absorber A is preferably 300 to 600, more preferably 360 to 600, further preferably 380 to 550, and further preferably 400 to 550.
[0091] The molecular weight of the ultraviolet absorber A can be determined from the atomic weight of the atoms constituting the ultraviolet absorber A. Alternatively, it can be measured by field desorption mass spectrometry (FD-MS). In this case, for example, it can be measured by the following method.
[0092] The device can use a gas chromatograph flight time mass analyzer JMD-T100GCV manufactured by JEOL Ltd. 10 mg of ultraviolet absorber is dissolved in 10 mL of chloroform to obtain an ultraviolet absorber solution. 1 μL of ultraviolet absorber solution is applied to the emitter of the device using a micro syringe, and the ultraviolet absorber is introduced into the device. Then, the molecules of the ultraviolet absorber are ionized to obtain a spectrum of the m / z values of the ions. The m / z value of the main peak of the spectrum is measured as the molecular ion of the ultraviolet absorber, and can be determined as the molecular weight of the ultraviolet absorber.
[0093] As the ultraviolet absorber A, for example, benzoate compounds, triazine compounds, benzotriazole compounds, etc. can be preferably used. Among them, from the viewpoint of easily obtaining a foamed particle molded body with excellent tensile strength, the ultraviolet absorber A preferably contains at least one selected from the group consisting of benzoate compounds and triazine compounds, and more preferably contains benzoate compounds and triazine compounds. In this case, the proportion of benzoate compounds and / or triazine compounds in the ultraviolet absorber A is preferably 50% by mass or more, more preferably 60% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more.
[0094] In addition, when the ultraviolet absorber A contains a benzoate compound and a triazine compound, the ratio of the content of the triazine compound to the content of the benzoate compound is preferably 0.1 to 0.8, and more preferably 0.2 to 0.6. In this case, a foamed particle molded body having better long-term weather resistance can be obtained.
[0095] In the case where the expanded particles contain ultraviolet absorber A, from the viewpoint of stably obtaining an expanded particle molded body showing excellent weather resistance for a long time, the content of ultraviolet absorber A in the expanded particles is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, further preferably 0.1% by mass or more, and further preferably 0.2% by mass or more. In addition, from the viewpoint of being able to stably obtain expanded particles with good in-mold formability, the content of the ultraviolet absorber A in the expanded particles is preferably 2% by mass or less, and more preferably 1% by mass or less. That is, in the case where the expanded particles contain ultraviolet absorber A, the content of ultraviolet absorber A in the expanded particles is preferably 0.01 to 2% by mass, more preferably 0.05 to 2% by mass, further preferably 0.1 to 1% by mass, and further preferably 0.2 to 1% by mass.
[0096] In addition, the expanded particles may contain an ultraviolet absorber other than the ultraviolet absorber A. On the other hand, from the viewpoint of stably obtaining expanded particles having good in-mold moldability, the content of the ultraviolet absorber other than the ultraviolet absorber A in the expanded particles in this case is preferably 40 parts by mass or less, more preferably 30 parts by mass or less, further preferably 20 parts by mass or less, and further preferably 10 parts by mass or less, relative to 100 parts by mass of the ultraviolet absorber A.
[0097] The content of the ultraviolet absorber A in the expanded particles can be measured in the same manner as the content of the hindered amine compound in the expanded particles described above, for example, by performing proton nuclear magnetic resonance (NMR) on the expanded particles. 1 H-NMR) measurements.
[0098] (Melting Point)
[0099] From the viewpoint of easily suppressing the migration of the ultraviolet absorber in the expanded particles in the resin and stably obtaining expanded particles having good in-mold moldability, the melting point of the ultraviolet absorber A is preferably 50°C or higher, more preferably 100°C or higher, further preferably 120°C or higher, and further preferably 130°C or higher. In addition, the melting point of the ultraviolet absorber A is preferably 220°C or lower, and more preferably 200°C or lower. That is, the melting point of the ultraviolet absorber A is preferably 50°C to 220°C, more preferably 100°C to 220°C, further preferably 120°C to 200°C, and further preferably 130°C to 200°C.
[0100] The melting point of the ultraviolet absorber A is measured based on JIS K 0064: 1992. Specifically, first, a sample of the ultraviolet absorber is placed in a glass capillary tube, and the sample is filled to the closed surface side of the capillary tube. Silicone oil is added to a glass heating container equipped with a thermometer, and the closed surface side of the capillary tube is immersed. Then, the silicone oil is continuously heated in such a manner that the heating rate of the silicone oil is constant, and the temperature at the time point when no solid can be visually confirmed inside the capillary tube is taken as the melting point.
[0101] Commercially available products can be used as the ultraviolet absorber A. Commercially available products of the ultraviolet absorber A include benzotriazole ultraviolet absorbers, such as "Tinuvin 99-2", "Tinuvin 326", "Tinuvin 384-2", "Tinuvin 900", "Tinuvin 928", and "Tinuvin 1130" manufactured by BASF; benzoate ultraviolet absorbers, such as "Tinuvin 120" manufactured by BASF and "Cyasorb UV-2908" manufactured by Solvay; and triazine ultraviolet absorbers, such as "Tinuvin 1577" manufactured by BASF and "Cyasorb UV-1164" manufactured by Solvay.
[0102] (Content of UV absorber A / Content of hindered amine compound)
[0103] From the viewpoint of stably obtaining expanded beads capable of producing expanded bead molded articles showing excellent weather resistance for a long period of time, when the expanded beads contain ultraviolet absorber A, the ratio of the content of ultraviolet absorber A in the expanded beads to the content of the hindered amine compound is preferably 0.1 or more, more preferably 0.3 or more, further preferably 0.6 or more, and further preferably 0.8 or more. Furthermore, from the viewpoint of stably obtaining expanded beads having good in-mold moldability, the ratio of the content of ultraviolet absorber A in the expanded beads to the content of the hindered amine compound is preferably 5 or less, more preferably 4 or less, further preferably 3 or less, and further preferably 2 or less. That is, the ratio of the content of ultraviolet absorber A in the expanded beads to the content of the hindered amine compound is preferably 0.1 to 5, more preferably 0.3 to 4, further preferably 0.6 to 3, and further preferably 0.8 to 2.
[0104] (Content of UV absorber A / Content of inorganic pigment)
[0105] From the viewpoint of stably obtaining expanded beads capable of producing an expanded bead molded body having a good appearance without color unevenness and showing excellent weather resistance for a long period of time, when the expanded beads contain an inorganic pigment, the ratio of the content of the ultraviolet absorber A in the expanded beads to the content of the inorganic pigment is preferably 0.01 or more, more preferably 0.05 or more, and further preferably 0.1 or more. In addition, from the viewpoint of stably obtaining an expanded bead molded body having excellent stretching properties, when the expanded beads contain an inorganic pigment, the ratio of the content of the ultraviolet absorber A in the expanded beads to the content of the inorganic pigment is preferably 5 or less, more preferably 4 or less, further preferably 3 or less, and further preferably 2 or less. That is, the ratio of the content of the ultraviolet absorber A in the expanded beads to the content of the inorganic pigment is preferably 0.01 to 5, more preferably 0.05 to 4, further preferably 0.1 to 3, and further preferably 0.1 to 2.
[0106] <Physical properties of expanded particles>
[0107] (Volume Density)
[0108] From the viewpoint of achieving a good balance between the mechanical strength and lightness of the expanded bead molded article, the bulk density of the expanded bead is preferably 10 kg / m 3 More preferably 15kg / m 3 More preferably, 20 kg / m 3 More preferably, 25 kg / m 3 More than, and preferably 500kg / m 3 Below, more preferably 100kg / m 3 Below, more preferably 70kg / m 3 Below, more preferably 60kg / m 3 That is, the bulk density of the expanded particles is preferably 10 to 500 kg / m 3 , more preferably 15 to 100 kg / m 3 , more preferably 20 to 70 kg / m 3 , more preferably 25 to 60 kg / m 3 .
[0109] The volume density of the foamed particles can be calculated as follows. Randomly take out foamed particles from the foamed particle group and put them into a 1L measuring cylinder. A large number of foamed particles are contained in a natural stacking state until the 1L mark is reached. The mass W1 [g] of the contained foamed particles is divided by the contained volume V1 (1 [L]) (W1 / V1), and the unit is converted to [kg / m 3 ], and the volume density of the foamed particles is calculated.
[0110] (Average bubble diameter)
[0111] From the viewpoint of improving the in-mold formability of the expanded particles and stably obtaining expanded particles capable of manufacturing a molded body having excellent stretching properties and showing excellent weather resistance for a long period of time, the average cell diameter of the expanded particles is preferably 50 μm or more, more preferably 55 μm or more, and further preferably 60 μm or more, and is preferably 250 μm or less, more preferably 200 μm or less, further preferably 150 μm or less, and further preferably 120 μm or less. That is, the average cell diameter of the expanded particles is preferably 50 to 250 μm, more preferably 55 to 200 μm, further preferably 60 to 150 μm, and further preferably 60 to 120 μm.
[0112] The average bubble diameter of the expanded particles can be measured by drawing a plurality of line segments from the outermost surface of the expanded particles through the center to the outermost surface on the opposite side in an enlarged photograph of a cross section of the expanded particles divided into two, and dividing the total length of the line segments by the total number of bubbles intersecting with each line segment. Specifically, the average bubble diameter of the expanded particles can be measured by the method described in the Examples.
[0113] The average cell diameter of the expanded particles can be adjusted to a desired range by adjusting the type and amount of the cell regulator added to the resin particles or the amount of the hindered amine compound added, or by adjusting the foaming pressure during foaming of the resin particles.
[0114] (Crystal Structure)
[0115] The foamed particles are preferably foamed particles formed by foaming resin particles that have not been surface-modified with an organic peroxide. In this case, foamed particles that can be molded in a mold at a relatively low molding pressure can be manufactured with good productivity. From this viewpoint, the foamed particles preferably have the following crystal structure: based on JIS K 7122: 1987, in the DSC curve obtained by heating from 23°C to 200°C at a heating rate of 10°C / min, a melting peak (intrinsic peak) inherent to the polypropylene resin and one or more melting peaks (high temperature peaks) on the high temperature side than the intrinsic peak appear. In addition, the foamed particles more preferably have the above crystal structure and satisfy the relationship of the following formula (1).
[0116] ΔHs≥ΔHi×0.86···(1)
[0117] (In formula (1), ΔHs is the heat of fusion of the high temperature peak of the surface layer of the expanded beads, and ΔHi is the heat of fusion of the high temperature peak inside the expanded beads.)
[0118] Furthermore, from the viewpoint of being able to perform in-mold molding at a relatively low molding pressure and stably obtaining a molded body having good stretching properties, the expanded particles preferably satisfy the formula (1) and the following formula (2).
[0119] ΔHi×1.2≥ΔHs···(2)
[0120] ΔHs can be measured by the same method as the method for measuring the heat of fusion at the high temperature peak of the foamed beads, except using a sample cut from the surface layer of the foamed beads. In addition, ΔHi can be measured by the same method as the method for measuring the heat of fusion at the high temperature peak of the foamed beads, except using a sample cut from the inside of the foamed beads without including the surface layer.
[0121] In addition, the surface layer of the foamed particles refers to the part within the range of 200 μm from the surface of the foamed particles toward the center of the foamed particles. In addition, when preparing the sample, a predetermined amount of sample can be prepared by cutting out the surface layer or the internal sample from a plurality of foamed particles and using it for measurement.
[0122] The melting peak can be specifically obtained by the following method: 1 to 3 mg of expanded particles are heated from 23°C to 200°C at a heating rate of 10°C / min using a differential scanning calorimeter to obtain a DSC curve, from which the melting peak (high temperature peak) can be confirmed.
[0123] The DSC curve in this case refers to a DSC curve obtained by heating the foamed particles by the measurement method (DSC curve in the first heating). In addition, the melting peak inherent to the resin (inherent peak) refers to a melting peak caused by the melting of crystals inherent to the polypropylene resin constituting the foamed particles. In addition, it can be considered that the inherent peak is a melting peak that appears due to the melting of crystals generally possessed by the polypropylene resin constituting the foamed particles.
[0124] On the other hand, the melting peak (high temperature peak) closer to the high temperature side than the inherent peak refers to the melting peak that appears on the high temperature side than the inherent peak in the first DSC curve. In the case of the appearance of this high temperature peak, it is inferred that there are secondary crystals in the resin. In addition, in the DSC curve (DSC curve in the second heating) obtained when the foamed particles are heated from 23°C to 200°C at a heating rate of 10°C / min (first heating), cooled from 200°C to 23°C at a cooling rate of 10°C / min, and then heated from 23°C to 200°C (second heating) again at a heating rate of 10°C / min, only the melting peak caused by the melting of the crystals inherent to the polypropylene resin as the base resin of the foamed particles appears. This inherent peak appears in both the DSC curve in the first heating and the DSC curve in the second heating, so by comparing the shapes of the first and second DSC curves and the positions of the peaks in each DSC curve, it is possible to confirm which peak is the inherent peak.
[0125] In addition, the foamed particles are preferably foamed particles in which only a melting peak (intrinsic peak) inherent to the polypropylene resin appears in a DSC curve during the second heating obtained by heating from 23°C to 200°C at a heating rate of 10°C / min, cooling from 200°C to 23°C at a cooling rate of 10°C / min, and then heating from 23°C to 200°C at a heating rate of 10°C / min.
[0126] (Heat of fusion of high temperature peak)
[0127] From the viewpoint of further expanding the range of molding conditions that can obtain a good foamed bead molded body, the melting heat of the high temperature peak of the foamed beads is preferably 5 J / g or more, more preferably 7 J / g or more, and more preferably 10 J / g or more, and is preferably 40 J / g or less, more preferably 30 J / g or less, and more preferably 20 J / g or less. That is, the melting heat of the high temperature peak of the foamed beads is preferably 5 to 40 J / g, more preferably 7 to 30 J / g, and more preferably 10 to 20 J / g.
[0128] The heat of fusion of the high temperature peak of the expanded beads can be measured by the above method. More specifically, it can be measured by the method described in the Examples.
[0129] (Crystallinity)
[0130] From the viewpoint of improving the in-mold formability of the foamed particles under the condition of low molding pressure, the crystallinity of the foamed particles is preferably 42% or less, more preferably 40% or less, and further preferably 38% or less. In addition, the lower limit of the crystallinity of the foamed particles is preferably about 20%, and from the viewpoint of being able to stably obtain a foamed particle molded body with good compression strength, etc., it is preferably 22%, and more preferably 25%. That is, the crystallinity of the foamed particles is preferably 20% to 42%, more preferably 22% to 40%, and further preferably 25% to 38%.
[0131] The crystallinity of the expanded particles was calculated by dividing the heat of fusion of the expanded particles by the heat of fusion of a complete crystal of polypropylene (207 J / g) (unit: %).
[0132] The heat of fusion of the expanded beads is calculated as the total heat of fusion of all melting peaks (endothermic peaks) appearing in the first DSC curve measured in accordance with JIS K 7122: 1987. More specifically, it can be measured by the method described in Examples.
[0133] The crystallinity of the expanded beads takes a value close to the crystallinity of the polypropylene resin used to produce the expanded beads, and therefore can be adjusted by adjusting the type of the polypropylene resin used.
[0134] As long as the effect of the present invention is not hindered, additives may be appropriately added to the expanded particles. Examples of additives include antioxidants, antistatic agents, conductive fillers, flame retardants, dyes, and bubble regulators. These additives can be contained in the expanded particles by, for example, adding them when granulating the resin particles.
[0135] As the bubble regulator, for example, inorganic powder or organic powder can be used. Examples of the inorganic powder include metal borate salts such as zinc borate and magnesium borate, and examples of the organic powder include fluororesin powders such as polytetrafluoroethylene. From the viewpoint of easily adjusting the average bubble diameter of the expanded particles to a desired range, metal borate salts are preferably used as the bubble regulator, and zinc borate is more preferably used.
[0136] When zinc borate is used, the number-based arithmetic mean particle size is preferably 0.5 μm to 10 μm, more preferably 1 μm to 8 μm. Based on the volume-based particle size distribution measured by the laser diffraction scattering method, the shape of the particles is assumed to be a sphere and converted into a number-based particle size distribution, thereby obtaining a number-based particle size distribution, and the particle size based on the number-based particle size distribution is arithmetic averaged, thereby the number-based arithmetic mean particle size of zinc borate can be calculated. In addition, the above-mentioned particle size refers to the diameter of a virtual sphere having the same volume as the particle.
[0137] From the viewpoint of being able to stably obtain expanded particles having a desired bulk density and a small deviation in bubble diameter, the blending amount of the bubble regulator in the resin particles is preferably 50 mass ppm or more, more preferably 100 mass ppm or more, and further preferably 150 mass ppm or more, and is preferably 5000 mass ppm or less, more preferably 2000 mass ppm or less, and further preferably 1500 mass ppm or less. That is, the blending amount of the bubble regulator in the resin particles is preferably 50 to 5000 mass ppm, more preferably 100 to 2000 mass ppm, and further preferably 150 to 1500 mass ppm.
[0138] The expanded particles may contain other polymers such as resins other than the polypropylene-based resin or elastomers within a range not inhibiting the objective effects of the present invention.
[0139] When the other polymer is contained, the content of the other polymer in the foamed particles is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 5 parts by mass or less, based on 100 parts by mass of the polypropylene resin.
[0140] The foamed particles may also have a welding layer on their surface for improving the welding property of the foamed particles during in-mold molding. The welding layer may be present on the entire surface of the foamed particles or on a part of the surface. As the resin constituting the welding layer, there may be exemplified a crystalline polyolefin resin having a lower melting point than the melting point of the polypropylene resin as the base resin of the foamed particles, an amorphous polyolefin resin having a lower softening point than the melting point of the polypropylene resin as the base resin of the foamed particles, an adhesive resin such as a polyurethane resin, and the like.
[0141] The method for forming the welding layer on the surface of the foamed particles is not particularly limited, and examples thereof include a method of foaming resin particles having a welding layer, or a method of attaching the welding layer to the foamed particles after the foamed particles are obtained. When the foamed particles are obtained by foaming resin particles having a welding layer, it is preferable to adopt a method of laminating the welding layer on the surface of the resin particles by co-extrusion when the resin particles are granulated.
[0142] [Method for producing expanded particles]
[0143] For example, the expanded particles of the present invention can be produced by releasing polypropylene resin particles containing a blowing agent and a hindered amine compound dispersed in an aqueous medium in a container together with the aqueous medium from the container into an atmosphere with a pressure lower than the pressure in the container to foam the resin particles. An example of a preferred production method is shown below.
[0144] A preferred method for producing the foamed particles of the present invention is to use a polypropylene resin having a crystallinity of 45% or less as a base resin, and to foam resin particles containing a hindered amine compound to produce the foamed particles, wherein the hindered amine compound has a structure represented by the following formula (I), and the content of the hindered amine compound in the foamed particles is 0.01% by mass to 4% by mass. In the production method, the resin particles containing a foaming agent in an aqueous medium dispersed in a container are released from the container together with the aqueous medium into a pressure atmosphere lower than the pressure in the container, thereby causing the resin particles to foam.
[0145] [Chemistry 3]
[0146]
[0147] (In formula (I), X represents an alkylene group, and Y1 and Y2 each independently represent a hydrocarbon group or a hydrocarbon group bonded via an oxygen atom.)
[0148] <Manufacturing of resin particles>
[0149] The resin particles used in the manufacture of the foamed particles of the present invention can be manufactured, for example, as follows. First, the polypropylene resin, the hindered amine compound, and other additives such as a bubble regulator, a pigment, and an ultraviolet absorber added as needed are supplied to an extruder, and heated and kneaded to form a resin melt. Next, the resin melt is extruded from the extruder and granulated. As a granulation method, a method based on a wire cutting method, a thermal cutting method, an underwater cutting method, etc. can be adopted. In this way, the resin particles can be obtained.
[0150] The average mass of each resin particle (the arithmetic mean value of each obtained by measuring the mass of 200 randomly selected particles) is preferably 0.1 mg or more, more preferably 0.3 mg or more, and further preferably 0.5 mg or more, and is preferably 10 mg or less, more preferably 5 mg or less, further preferably 3 mg or less, and further preferably 2 mg or less. That is, the average mass of each resin particle is preferably 0.1 to 10 mg, more preferably 0.3 to 5 mg, further preferably 0.5 to 3 mg, and further preferably 0.5 to 2 mg. In addition, the outer shape of the resin particles is not particularly limited as long as the desired purpose of the present invention can be achieved, but is preferably cylindrical.
[0151] When the outer shape of the resin particles is cylindrical, the particle diameter (length in the extrusion direction) of the resin particles is preferably 0.1 to 3.0 mm, and more preferably 0.3 to 1.5 mm. In addition, the ratio (L / D) of the length L of the resin particles in the extrusion direction to the length D in the direction perpendicular to the extrusion direction of the resin particles (diameter of the resin particles) is preferably 0.5 to 5.0, and more preferably 1.0 to 3.0.
[0152] The particle size, L / D, and average mass of the resin particles in the strand cutting method can be adjusted by appropriately changing the extrusion speed, the pulling speed, the cutting speed, etc. when extruding the resin melt and cutting it.
[0153] <Manufacturing of expanded particles>
[0154] A preferred method for producing expanded particles includes, as a first step, a dispersing step of dispersing resin particles containing a hindered amine compound and, if necessary, other additives in an aqueous medium containing an inorganic dispersant in a container such as a pressure container.
[0155] As a dispersion medium for dispersing the resin particles in the pressure vessel, an aqueous dispersion medium is used. The aqueous dispersion medium is a dispersion medium with water as the main component. The proportion of water in the aqueous dispersion medium is preferably 70% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, and may also be 100% by mass. As a dispersion medium other than water in the aqueous dispersion medium, ethylene glycol, glycerol, methanol, ethanol, etc. may be cited.
[0156] It is preferred to add a dispersant to the above-mentioned aqueous medium so that the resin particles heated in the container do not fuse to each other. As a dispersant, any organic dispersant or inorganic dispersant can be used as long as it is a dispersant that prevents the resin particles from fusing in the container, but an inorganic dispersant is preferred. From the perspective of easy handling, a particulate inorganic dispersant is more preferred. For example, natural or synthetic clay minerals such as kaolin, mica, and clay, aluminum oxide, titanium oxide, basic magnesium carbonate, basic zinc carbonate, calcium carbonate, iron oxide, etc. can be cited. Among them, natural or synthetic clay minerals are preferred. One dispersant can be used alone, or two or more can be used in combination. The amount of dispersant added is preferably 0.001 to 5 parts by mass relative to 100 parts by mass of resin particles.
[0157] In addition, depending on the type of hindered amine compound mixed in the resin particles, the inorganic dispersant in the dispersion medium is easily attached to the surface of the resin particles, so that the inorganic dispersant attached to the surface of the obtained foamed particles increases, and thus sometimes the welding of the foamed particles during in-mold molding is deteriorated. On the other hand, in the present invention, by using a specific hindered amine compound, the foamed particles are well welded to each other even under relatively low molding pressure conditions, and foamed particles that can be used to manufacture foamed particle molded bodies within a relatively wide molding pressure range can be obtained. In addition, a molded body with a good welding state and long-term weather resistance can be obtained.
[0158] When a dispersant is used, it is preferred to use an anionic surfactant such as sodium dodecylbenzenesulfonate, sodium alkylsulfonate, sodium oleate, or aluminum sulfate in combination as a dispersant. The amount of the dispersant added is preferably 0.001 to 1 part by mass per 100 parts by mass of the resin particles.
[0159] In the method for producing expanded particles, it is preferred that after the dispersion step, there is a step of adding a foaming agent to the aqueous medium. As a foaming agent for foaming the resin particles, a physical foaming agent is preferably used. As a physical foaming agent, inorganic physical foaming agents and organic physical foaming agents can be mentioned. As an inorganic physical foaming agent, carbon dioxide, air, nitrogen, helium, argon, etc. can be mentioned. As an organic physical foaming agent, aliphatic hydrocarbons such as propane, n-butane, isobutane, n-pentane, isopentane, and hexane; cyclic aliphatic hydrocarbons such as cyclopentane and cyclohexane; halogenated hydrocarbons such as ethyl chloride, 2,3,3,3-tetrafluoropropene, trans-1,3,3,3-tetrafluoropropene, and trans-1-chloro-3,3,3-trifluoropropene can be mentioned. The foaming agent can be used alone or in combination of two or more. In addition, an inorganic physical foaming agent can also be mixed with an organic physical foaming agent. Among them, from the viewpoint of environmental load and handleability, the blowing agent is preferably an inorganic physical blowing agent, and more preferably carbon dioxide.
[0160] The amount of the foaming agent added is preferably about 0.1 to 30 parts by mass, more preferably 0.5 to 15 parts by mass, based on 100 parts by mass of the resin particles, although it depends on the type of the foaming agent, the desired bulk density of the foamed particles, and the like.
[0161] The foaming agent adding step can obtain resin particles containing the foaming agent. In the foaming agent adding step, for example, the resin particles are dispersed in an aqueous dispersion medium in a pressure vessel, the foaming agent is pressed into the pressure vessel, the pressure vessel is heated and pressurized, and maintained at a predetermined temperature and pressure, so that the foaming agent can be impregnated into the resin particles.
[0162] In a preferred method for producing expanded particles, after the foaming agent adding step, a foaming step is included: releasing the polypropylene-based resin particles containing the foaming agent together with an aqueous medium from a container to foam them.
[0163] The pressure (internal pressure) in the pressure container during foaming is preferably 0.5 MPa (G) or more, more preferably 0.8 MPa (G) or more, and preferably 4 MPa (G) or less, more preferably 3 MPa (G) or less. In addition, G in the unit represents gauge pressure. The pressure in the pressure container can be adjusted by adding a foaming agent in a closed container.
[0164] In addition, the temperature is preferably raised to 100-200°C, more preferably to 130-160°C, and preferably maintained at this temperature for about 5-30 minutes, after which the resin particles containing the foaming agent are released from the pressure vessel into a pressure atmosphere lower than the pressure in the pressure vessel (e.g., atmospheric pressure) to perform foaming.
[0165] Furthermore, expanded beads having a crystal structure showing a unique peak and a high-temperature peak in the first DSC curve can be produced, for example, as follows.
[0166] First, the resin particles dispersed in the dispersion medium in the pressure vessel are heated to a temperature of (melting point of the polypropylene resin constituting the resin particles - 15°C) to (melting point of the polypropylene resin constituting the resin particles + 10°C), and are kept at this temperature for a sufficient time, preferably for about 10 to 60 minutes (holding step). Then, the resin particles that have undergone the holding step are foamed to obtain foamed particles showing the above-mentioned melting peak.
[0167] In the manufacture of the foamed particles, the resin particles which have been through the holding step may be prepared in advance, and the foamed particles may be obtained by foaming the resin particles which have been through the holding step. In addition, for example, the resin particles may be subjected to the holding step as part of the dispersion step or the foaming agent addition step, and the resin particles which have been through the holding step may be foamed to obtain the foamed particles.
[0168] From the viewpoint of improving the productivity of foamed particles, it is preferred that, after heating the resin particles dispersed in the dispersion medium in the pressure vessel in the presence of a foaming agent and performing the above-mentioned holding step, the contents of the pressure vessel are released from the pressure vessel into a pressure atmosphere lower than the pressure in the pressure vessel, thereby foaming the resin particles, thereby obtaining foamed particles showing the above-mentioned melting peak.
[0169] The expanded particles obtained as described above can also be pressurized with air or the like to increase the pressure (internal pressure) in the bubbles of the expanded particles, and then heated with steam or the like to expand them (two-step expansion), thereby obtaining expanded particles with a higher expansion ratio (lower bulk density).
[0170] [Expanded Bead Molded Article]
[0171] The foamed particle molded article of the present invention (hereinafter also referred to as "foamed particle molded article" or "molded article") is an in-mold molded article of foamed particles, which is formed by in-mold molding of the foamed particles. Specifically, it is formed by in-mold molding of the following foamed particles: a polypropylene resin is used as a base resin and contains a hindered amine compound, the polypropylene resin has a crystallinity of 45% or less, the hindered amine compound has a structure represented by the following formula (I), and the content of the hindered amine compound in the foamed particles is 0.01 mass % or more and 4 mass % or less.
[0172] [Chemistry 4]
[0173]
[0174] (In formula (I), X represents an alkylene group, and Y1 and Y2 each independently represent a hydrocarbon group or a hydrocarbon group bonded via an oxygen atom.)
[0175] The expanded particle molded body is an in-mold molded body of the expanded particles, preferably obtained by in-mold molding of the expanded particles. The in-mold molding method can be performed by filling the expanded particles into a molding die and heating and molding using a heating medium such as steam. Specifically, after the expanded particles are filled into the molding die, a heating medium such as steam is introduced into the molding die, thereby heating the expanded particles to make them foamed twice and welded to each other, thereby obtaining an expanded particle molded body with a shape given to the molding space. As a method for filling the expanded particles into the molding die, a known method can be adopted. The filling of the foamed particles into the forming mold can be exemplified by: the slit filling method, in which the mold is opened in advance before the foamed particles are filled into the mold to expand the forming space, and the mold is closed after filling to compress the foamed particles (for example, Japanese Patent Publication No. 46-38359); the pressurized filling method, in which the foamed particles are pre-pressurized with a pressurized gas such as air to increase the pressure in the bubbles of the foamed particles, and the pressure in the foamed particles is adjusted to a pressure 0.01 to 0.3 MPa higher than the atmospheric pressure, and then the foamed particles are filled into the forming mold under atmospheric pressure or under reduced pressure (for example, Japanese Patent Publication No. 51-22951). In addition, the forming can also be performed by a pressurized forming method (for example, Japanese Patent Publication No. 51-22951) in which a heating medium such as steam is supplied into the mold to heat and fuse the foamed particles. In addition, it is also possible to fill the forming mold with expanded particles pressurized to a pressure above atmospheric pressure by using a compression filling method (Japanese Patent Publication No. 4-46217) in which expanded particles pressurized to a pressure above atmospheric pressure are filled in the forming mold using compressed gas. In addition, it is also possible to fill the expanded particles by using a normal pressure filling method (Japanese Patent Publication No. 6-49795) or a method combining the above methods (Japanese Patent Publication No. 6-22919) etc., in which expanded particles with high secondary foaming power obtained under special conditions are filled into the mold cavity of the forming mold under atmospheric pressure or under reduced pressure. In addition, as a heating method using steam or the like, heat forming can be performed by a known method using a method that appropriately combines heating methods such as single-side heating, opposite-side heating, and main heating.
[0176] <Density>
[0177] From the viewpoint of stably obtaining a lightweight expanded bead molded article with excellent stretch properties, the density of the expanded bead molded article is preferably 10 kg / m 3 More preferably 20kg / m 3 More preferably, 30 kg / m 3 More than, and preferably 500kg / m 3 Below, more preferably 200kg / m 3 Below, more preferably 100kg / m 3 Below, more preferably 70kg / m 3That is, the density of the expanded bead molded article is preferably 10 to 500 kg / m 3 , more preferably 20 to 200 kg / m 3 , more preferably 20 to 100 kg / m 3 , more preferably 30 to 100 kg / m 3 .
[0178] The density of the expanded bead molded article is calculated by dividing the mass of the expanded bead molded article by the volume calculated based on the size. Specifically, the density can be measured by the method described in Examples.
[0179] <Ratio (tensile strength / density)>
[0180] The ratio of the tensile strength of the expanded bead molded article to the density of the expanded bead molded article (tensile strength / density) is preferably 10 kPa / [kg / m 3 ] or more, more preferably 13 kPa / [kg / m 3 ] or more, more preferably 15 kPa / [kg / m 3 ] and above, and there is no upper limit, but in practice it is 30 kPa / [kg / m 3 ] or less, preferably 25 kPa / [kg / m 3 That is, the ratio (tensile strength / density) of the molded body is preferably 10 to 30 kPa / [kg / m 3 ], more preferably 13 to 25 kPa / [kg / m 3 ], more preferably 15 to 25 kPa / [kg / m 3 By making the ratio of the tensile strength of the foamed bead molded body to the density of the foamed bead molded body within the above range, a molded body having a good welding state, excellent tensile properties and stably exhibiting long-term weather resistance is obtained, which is preferred.
[0181] The tensile strength of the expanded bead molded body is related to the fusion state of the expanded bead molded body, which means that if the density of the molded body is the same, the greater the tensile strength, the higher the fusion property of the expanded bead molded body. On the other hand, since the tensile strength of the molded body also depends on the density of the molded body, the fusion state of the molded body can be appropriately evaluated by using the ratio of the tensile strength of the expanded bead molded body to the density.
[0182] The tensile strength of the expanded particle molded article can be measured based on JIS K 6767:1999, for example, by the method described in the examples. In addition, the tensile strength refers to the maximum nominal stress generated until the test piece is cut in the tensile test. In addition, the ratio of the tensile strength to the density (tensile strength per unit density) can be calculated by dividing the measured tensile strength value by the density value.
[0183] <Tensile elongation>
[0184] The tensile elongation of the foamed particle molded body is preferably 15% or more, more preferably 18% or more, and further preferably 20% or more. In addition, there is no restriction on the upper limit, but it is practically 50% or less, preferably 40% or less. That is, the tensile elongation of the foamed particle molded body is preferably 15% to 50%, more preferably 18% to 40%, and further preferably 20% to 35%. By making the tensile elongation of the foamed particle molded body within the said range, the foamed particles are well welded to each other, and in particular, the foamed particles inside the molded body are also well welded. As a result, the molded body has excellent durability, so it is preferred.
[0185] The tensile elongation of the expanded bead molded article can be measured based on JIS K 6767: 1999, for example, by the method described in Examples. The tensile elongation refers to the elongation of a test piece when the test piece is cut in a tensile test.
[0186] The foamed bead molded article of the present invention has excellent long-term weather resistance and excellent tensile properties. Therefore, the foamed bead molded article of the present invention can be used as an impact absorbing material, a heat insulating material, and various packaging materials, and can be used for food transport containers, packaging and cushioning materials for electrical and electronic components, vehicle parts such as automobile bumpers, building parts such as residential heat insulating materials, sundries, furniture, sporting goods, and the like.
[0187] Example
[0188] Next, the present invention will be described in further detail by way of examples, but the present invention is not limited to these examples at all.
[0189] [Measurement and evaluation]
[0190] The following measurements and evaluations were performed on the polypropylene resins, hindered amine compounds, ultraviolet absorbers, expanded particles, and expanded particle molded articles used in the examples and comparative examples. The expanded particles or expanded particle molded articles were evaluated after they were left for 2 days under the conditions of a relative humidity of 50%, 23°C, and 1 atm and conditioned.
[0191] <Polypropylene resin>
[0192] (Crystallinity)
[0193] The crystallinity of the polypropylene-based resin is calculated by dividing the heat of fusion of the polypropylene-based resin by the heat of fusion of a complete crystal of polypropylene (207 J / g) (unit: %).
[0194] The heat of fusion of the polypropylene resin is obtained from a DSC curve obtained by differential scanning calorimetry (DSC) based on JIS K 7122: 1987. Specifically, "(2) The case of measuring the melting temperature after a certain heat treatment" is used as the state adjustment of the test piece. Under the condition of a nitrogen inflow of 30 mL / min, the test piece is heated from 23°C to 200°C at a heating rate of 10°C / min, then maintained at this temperature for 10 minutes, then cooled to 23°C at a cooling rate of 10°C / min, and heated to 200°C again at a heating rate of 10°C / min to obtain a DSC curve (DSC curve at the time of the second heating). The point at a temperature of 80°C on the obtained DSC curve at the time of the second heating is defined as α, and the point on the DSC curve corresponding to the melting end temperature is defined as β. The area of the portion surrounded by the DSC curve and the line segment (α-β) in the interval between the points α and β is measured and is taken as the heat of fusion of the polypropylene resin.
[0195] (Melting Point)
[0196] A polypropylene resin was used as a test piece, and the melting point of the polypropylene resin was measured based on JIS K 7121: 2012. Specifically, "(2) After a certain heat treatment, the melting temperature was measured" was used as the state adjustment of the test piece. Under the condition of a nitrogen inflow of 30 mL / min, the test piece was heated from 23°C to 200°C at a heating rate of 10°C / min, then kept at this temperature for 10 minutes, then cooled to 23°C at a cooling rate of 10°C / min, and heated to 200°C again at a heating rate of 10°C / min, thereby obtaining a DSC curve (DSC curve at the second heating). Next, the vertex temperature of the melting peak in the DSC curve was calculated, and the value was used as the melting point of the polypropylene resin. In the case where multiple melting peaks appear in the DSC curve, the vertex temperature of the melting peak with the highest height based on the baseline is used as the melting point.
[0197] (MFR)
[0198] The MFR of the polypropylene-based resin is measured under the conditions of a temperature of 230° C. and a load of 2.16 kg in accordance with JIS K 7210-1:2014.
[0199] <Foamed particles>
[0200] (Volume Density)
[0201] Regarding the bulk density of the foamed particles, the loose volume is about 500cm 3 Fill the measuring cylinder with the foamed bead group and tap the bottom of the measuring cylinder on the ground several times to stabilize the filling height of the foamed bead group in the measuring cylinder. Read the loose volume of the foamed bead group indicated by the measuring cylinder scale and refer to it as V1[L]. Next, measure the mass of the foamed bead group and refer to it as W1[g].
[0202] The mass W1[g] of the expanded particles is divided by the volume V1 to calculate (W1 / V1), and the unit is converted to [kg / m 3 ], and thus the volume density of the foamed particles is calculated.
[0203] (Average bubble diameter)
[0204] The average bubble diameter of the foamed particles is measured as follows. 30 foamed particles are randomly selected from the foamed particle group. The foamed particles are cut in half by passing through their center, and an enlarged photo of each cross section is taken. In each cross-sectional photo, four line segments are drawn from the outermost surface of the foamed particle through the center to the outermost surface of the opposite side, so that the angle formed by the two adjacent line segments is equal. The number of bubbles intersecting with each line segment is measured respectively, and the total length of the four line segments is divided by the total number of bubbles intersecting with the line segments, thereby obtaining the average bubble diameter of each foamed particle. These values are arithmetic averaged, thereby obtaining the average bubble diameter of the foamed particles.
[0205] (Heat of fusion and heat of fusion of high temperature peak)
[0206] The heat of fusion of the expanded particles and the heat of fusion of the high temperature peak were measured by heat flux differential scanning calorimetry based on JIS K 7122: 1987. Specifically, about 2 mg of the expanded particles were collected and measured by a differential scanning calorimeter (DSC7020, manufactured by Hitachi High-Technologies Corporation) at a temperature increase of 10°C / min from 23°C to 200°C to obtain a DSC curve having one or more melting peaks. In the following description, the inherent peak inherent to the resin is referred to as A, and the high temperature peak appearing on the higher temperature side than the peak is referred to as B.
[0207] Draw a straight line (α-β) connecting point α corresponding to 80°C on the DSC curve and point β on the DSC curve corresponding to the melting end temperature T of the foamed particles. In addition, the above-mentioned melting end temperature T refers to the end point on the high temperature side of the high temperature peak B, which refers to the intersection of the high temperature peak and the high temperature side baseline. Next, from point γ on the DSC curve corresponding to the valley between the above-mentioned intrinsic peak A and the high temperature peak B, draw a straight line parallel to the vertical axis of the graph, and the point where it intersects with the above-mentioned straight line (α-β) is set as δ.
[0208] The area of the portion surrounded by the curve of the high temperature peak B part of the DSC curve, the line segment (δ-β) and the line segment (γ-δ) is obtained, and the melting heat of the high temperature peak is calculated from the area. In addition, the area of the portion surrounded by the curve of the intrinsic peak A part of the DSC curve, the curve of the high temperature peak B part and the line segment (α-β) is obtained, and the melting heat (total melting heat) of the foamed particles is calculated from the area. For three different test pieces, the melting heat of the above-mentioned foamed particles and the melting heat of the high temperature peak are measured, and the arithmetic mean of the obtained values is taken as the melting heat of the foamed particles and the melting heat of the high temperature peak.
[0209] (Crystallinity)
[0210] The crystallinity of the expanded particles was calculated by dividing the heat of fusion of the expanded particles (total heat of fusion) by the heat of fusion of complete crystals of polypropylene (207 J / g) (unit: %).
[0211] (The heat of fusion of the high temperature peak of the surface layer of the expanded bead (ΔHs) and the heat of fusion of the high temperature peak inside the expanded bead (ΔHi))
[0212] In each of Examples and Comparative Examples, a portion ranging from the surface of the expanded beads to 200 μm toward the center of gravity of the expanded beads was cut out from a plurality of expanded beads to prepare a sample of about 2 mg. This sample was referred to as the expanded bead surface layer portion.
[0213] In each of the Examples and Comparative Examples, the interior of the foamed beads was cut out from a plurality of foamed beads so as not to include the surface layer portion, and a sample of about 2 mg was prepared. This sample was used as the interior of the foamed beads.
[0214] The heat flux differential scanning calorimetry was performed on the surface layer of the expanded beads and the interior of the expanded beads in the same manner as in the above <Heat of Fusion of Expanded Beads and Heat of Fusion of High-Temperature Peak> to obtain the heat of fusion of the high-temperature peak.
[0215] The melting heat of the high temperature peak of the surface layer of the foamed beads is ΔHs, and the melting heat of the high temperature peak inside the foamed beads is ΔHi. The value of 0.86 times ΔHi and the value of 1.2 times ΔHi are calculated and set as ΔHi×0.86 and ΔHi×1.2, respectively. The results are shown in Tables 1 and 2.
[0216] (Steam pressure range (molding pressure range that can produce qualified products))
[0217] The foamed particle molded body is molded by changing the molding pressure (molding steam pressure) by 0.01 MPa each time by the method described later in the <Manufacturing of Foamed Particle Molding Body>, and the molded particle molded body is evaluated for the items of weldability, surface appearance (gap = degree of voids), and recovery (recovery of expansion or contraction after molded body molding). The case where the benchmark shown below is reached is considered qualified, and the steam pressure at which all items are qualified is taken as the steam pressure range. The wider the range from the lower limit value to the upper limit value of the moldable steam pressure, the wider the moldable range, and the more preferred.
[0218] 《Weldability》
[0219] Bend the obtained foamed bead molded body to break it, and calculate the number of foamed particles (C1) existing on the fracture surface and the number of destroyed foamed particles (C2). Calculate the ratio of the number of destroyed foamed particles to the number of the above-mentioned foamed particles (C2 / C1×100) as the material destruction rate. Use different test pieces to carry out the above measurement 5 times and calculate the material destruction rate of each. The material destruction rate obtained by taking the arithmetic average of them is considered to be qualified when it is 80% or more, and is considered to be unqualified when it is less than 80%.
[0220] Surface Appearance
[0221] Draw a 100 mm × 100 mm square in the center of the plate surface of the obtained expanded bead molded body, and draw a line from one corner of the square to the diagonal line. Count the number of gaps (gaps) larger than 1 mm × 1 mm on the line. If the number of gaps is less than 5 and the surface has no unevenness, it is considered acceptable, otherwise it is considered unacceptable.
[0222] Resilience
[0223] The thickness of the flat plate-shaped foamed bead molded body with a length of 250 mm, a width of 200 mm, and a thickness of 50 mm obtained by in-mold molding is measured near the four corners (10 mm inside the center direction from the corner to the plate surface) and the thickness of the center of the molded body (the intersection of the line that divides the molded body into two equal parts in the longitudinal direction and the line that divides it into two equal parts in the transverse direction). Next, calculate the ratio (%) of the thickness of the center part to the thickness of the thickest part near the four corners. If the ratio is 95% or more, it is qualified, and if it is less than 95%, it is unqualified.
[0224] <Expanded Bead Molded Article>
[0225] (density)
[0226] The density of the foamed bead molded body is measured as follows. First, the foamed bead molded body is placed under the conditions of 50% relative humidity, 23°C, and 1 atm for 2 days. Then, its mass is measured and taken as W [g]. Then, based on the size of the foamed bead molded body, the volume V [cm 3 ]. The mass W [g] of the foamed particle molded body is divided by the volume V to calculate (W / V), and the unit is converted to [kg / m 3 ], and thus the density of the foamed particle molding is calculated.
[0227] (Tensile test)
[0228] The tensile test of the expanded bead molded article was conducted in accordance with JIS K 6767:1999 under the following conditions.
[0229] A vertical slicer is used to make slices from a foamed bead molded body or a foamed bead molded body irradiated with light under the light irradiation conditions of the weather resistance evaluation described later, in a manner that the epidermis on the irradiated side remains. A punching die is used to make a dumbbell-shaped No. 1 test piece (distance between markings 40mm, width 10mm, thickness 10mm) from the slice. The test piece is subjected to a tensile test at a tensile speed of 500mm / min, and the maximum load and the distance between markings during cutting are measured. The maximum nominal stress in the tensile test is taken as the tensile strength, and the elongation at the time of the test piece breaking ([distance between markings at cutting-distance between markings before the test] ÷ distance between markings before the test × 100) is taken as the tensile elongation. In addition, a Tensilon universal testing machine (manufactured by Orientec Co., Ltd.) is used as a measuring device. In addition, the tensile strength per density (the ratio of the tensile strength of the foamed bead molded body to the density of the foamed bead molded body [tensile strength / density]) is obtained by dividing the maximum tensile strength by the density.
[0230] (Weather resistance evaluation)
[0231] The molded article was irradiated with light under the following conditions based on JIS K 7350-2: 2008. The weather resistance of the expanded bead molded article was evaluated by measuring tensile properties (tensile strength, tensile elongation, tensile strength per density) of the molded article after light irradiation by a tensile test and observing changes in appearance (changes before and after light irradiation).
[0232] "Light exposure conditions"
[0233] Device used: Eye Super Xenon Tester XER-W83, manufactured by Iwasaki Electric Co., Ltd.
[0234] Light source: Xenon arc lamp
[0235] Filter: Inner filter: Quartz glass; Outer filter: Borosilicate glass
[0236] Irradiance: 120W / m 2
[0237] Radiation time: 330 hours (equivalent to 0.5 years of sunlight) or 1980 hours (equivalent to 3 years of sunlight)
[0238] Blackboard temperature: 63°C
[0239] Spray cycle: 18 minutes of water spray within 120 minutes (18 minutes of light irradiation and water spray after 102 minutes of light irradiation)
[0240] Humidity in the tank: 50%
[0241] Test piece size: 150mm×70mm×10mm
[0242] Appearance Evaluation
[0243] The expanded bead molded article irradiated with light as described above was evaluated according to the following criteria using the appearance of the molded article before the light irradiation as a standard product.
[0244] A: No change in appearance. No powder was found on the hand when touching the surface of the molded body.
[0245] B: No change in appearance was observed visually, but powder generated by resin pulverization adhered to the hand when the surface of the molded article was touched.
[0246] C: Resin chalking is clearly observed, or powder generated by the chalking of the resin significantly adheres to the hand when the surface of the molded article is touched.
[0247] [raw material]
[0248] The raw materials used in Examples and Comparative Examples are as follows.
[0249] <Polypropylene resin>
[0250] PP1: Ethylene-propylene-butene random copolymer, ethylene content 4.3% by mass, butene content 3.0% by mass, crystallinity 38%, melting point 140°C, MFR 7g / 10min
[0251] PP2: Ethylene-propylene random copolymer, ethylene content 3.1% by mass, crystallinity 36%, melting point 141°C, MFR 7g / 10min
[0252] PP3: Ethylene-propylene random copolymer, ethylene content 3.4% by mass, crystallinity 30%, melting point 139°C, MFR 7g / 10min
[0253] PP4: propylene homopolymer, crystallinity 50%, melting point 162°C, MFR 18g / 10min
[0254] <Hindered amine compounds>
[0255] HALS1: NOR type hindered amine, trade name "Tinuvin 123", manufactured by BASF, molecular weight 737, wherein in formula (I), X represents an octylene group, and Y1 and Y2 each represent an octyl group bonded via an oxygen atom.
[0256] [Chemistry 5]
[0257]
[0258] HALS2: NR type hindered amine, trade name "Tinuvin 765", manufactured by BASF, molecular weight 509, in formula (I), X represents an octylene group, and Y1 and Y2 each represent a methyl group.
[0259] [Chemistry 6]
[0260]
[0261] HALS3: NH type hindered amine, trade name "Tinuvin 770", manufactured by BASF, molecular weight 481, wherein X represents an octylene group, and Y1 and Y2 each represent a hydrogen atom.
[0262] [Chemistry 7]
[0263]
[0264] HALS4: NH type hindered amine, trade name "Uvinul4050", manufactured by BASF, molecular weight 451
[0265] [Chemistry 8]
[0266]
[0267] HALS5: NH type hindered amine, trade name "Chimassorb 944", manufactured by BASF, polystyrene equivalent number average molecular weight 2550
[0268] [Chemistry 9]
[0269]
[0270] <Ultraviolet light absorber>
[0271] UVA1: Benzoate-based UV absorber, trade name "Tinuvin 120", 2,4-di-tert-butylphenyl 3,5-di-tert-butyl-4-hydroxybenzoate, manufactured by BASF, molecular weight 439, melting point 195°C
[0272] [Chemistry 10]
[0273]
[0274] UVA2: Triazine ultraviolet absorber, trade name "Tinuvin 1577", 2-[4,6-diphenyl-1,3,5-triazine-2-yl]-5-(hexyloxy)phenol, manufactured by BASF, molecular weight 426, melting point 148°C
[0275] [Chemistry 11]
[0276]
[0277] UVA3: Benzotriazole ultraviolet absorber, trade name "Tinuvin 326", 2-tert-butyl-6-(5-chloro-2H-benzotriazole-2-yl)-4-methylphenol, manufactured by BASF, molecular weight 316, melting point 140°C
[0278] [Chemistry 12]
[0279]
[0280] UVA4: A mixture of UVA1 and UVA2 (UVA1: UVA2 = 1:1)
[0281] [Manufacturing of expanded particles]
[0282] Examples 1 to 9, Comparative Examples 2 to 9
[0283] An extruder with an inner diameter of 26 mm and a wire harness forming die attached to the downstream side was prepared. The resin shown in Table 1 or 2, the hindered amine compound shown in Table 1 or 2, zinc borate (arithmetic mean particle size based on number: 7 μm) as a bubble regulator, and carbon black (furnace black, primary particle size: 15 nm) were supplied to the extruder and melt-kneaded to form a resin melt. In addition, each additive was supplied so that the content of zinc borate in the foamed particles was 500 mass ppm, the content of carbon black as an inorganic pigment in the foamed particles was the content shown in Table 1 or 2, and the content of the hindered amine compound in the foamed particles was the content shown in Table 1 or 2.
[0284] The obtained resin melt was extruded from a strand forming die into a strand, and the extruded strand was water-cooled and cut with a pelletizer to obtain cylindrical resin particles each having an average mass of 1.0 mg.
[0285] Into a 5 L pressure vessel were placed 500 g of the resin particles, 3.5 L of water as a dispersion medium, 3 g of kaolin as a dispersant, and 0.2 g of sodium dodecylbenzenesulfonate (trade name: Neogen, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) as a surfactant.
[0286] Next, carbon dioxide is pressed into the pressure vessel as a foaming agent and pressurized until the gauge pressure reaches 2.5 MPa (G). Next, the contents of the pressure vessel are heated to the foaming temperature (146°C) at a heating rate of 2°C / min while stirring. The temperature is then maintained for 15 minutes. The high-temperature peak heat (obtained from the endothermic curve based on DSC measurement) can be adjusted by maintaining the temperature and the holding time. Then, the contents of the sealed container are released to atmospheric pressure to obtain foamed particles. The measurement results of the physical properties of the obtained foamed particles are shown in Table 1 or 2. In addition, the "vapor pressure range" in Tables 1 and 2 refers to the range of vapor pressures in which the in-mold formability of the foamed particles is excellent and qualified products can be obtained based on the above-mentioned evaluation method.
[0287] [Manufacturing of Expanded Bead Molded Article]
[0288] The expanded beads are filled into a mold capable of forming a flat plate of 250 mm in length, 200 mm in width and 50 mm in thickness, and heated by the following heating method. First, steam is supplied to the mold with the discharge valves provided on both sides of the mold open, thereby performing preliminary heating (exhaust process). Thereafter, steam is supplied from one side of the mold for heating, and further steam is supplied from the other side of the mold for heating. Next, steam is supplied from both sides of the mold for heating at a predetermined molding heating steam pressure (main heating). After the main heating is completed, the pressure is released, and after water cooling until the pressure generated on the molding surface of the mold is 0.04 MPa (G), the mold is opened and the expanded bead molded body is taken out. The obtained molded body is aged in an oven at 80°C for 12 hours to obtain an expanded bead molded body. The measurement results of the physical properties of the obtained expanded bead molded body are shown in Tables 1 or 2. In Examples 1 to 4, Comparative Examples 2 to 4 and Comparative Examples 7 to 9 using polypropylene resins with low crystallinity, the steam pressure range of the expanded beads is different depending on the type of hindered amine compound added. In addition, compared with the expanded particles of Comparative Examples 2 to 4 and Comparative Examples 7 to 9 containing hindered amine compounds not having a structure represented by formula (I), the expanded particles of Examples 1 to 4 containing hindered amine compounds having a structure represented by formula (I) have a wide vapor pressure range and excellent in-mold moldability.
[0289] Embodiments 10 to 15
[0290] Expanded beads and expanded bead molded articles were obtained in the same manner as in Example 1 except that the ultraviolet absorbers shown in Table 1 were added in the amounts shown in Table 1. Table 1 shows the results of measurement of physical properties of the obtained expanded beads and expanded bead molded articles.
[0291] Example 16
[0292] After the foaming process of Example 1, the following two-step foaming process is performed. The foamed particles obtained in the foaming process of Example 1 are filled with foamed particles (hereinafter referred to as one-step foamed particles) after being aged at 60°C for 12 hours in a pressurizable pressure container, and the pressure in the pressure container is increased from normal pressure (atmospheric pressure), and the foamed particles are pressurized to 0.6MPa(G). The foamed particles are maintained in a pressurized state for 12 hours to increase the pressure inside the bubbles of the foamed particles. Then, the one-step foamed particles are taken out of the pressure container to obtain one-step foamed particles whose bubbles have an internal pressure of 0.5MPa(G). Then, the one-step foamed particles are supplied to a two-step foaming device. Steam is supplied to the device to foam the one-step foamed particles to obtain a volume density of 27kg / m 3 The results of measuring the physical properties of the obtained expanded particles are shown in Table 1.
[0293] The obtained expanded particles were placed in a pressurizable pressure container and pressurized to increase the pressure in the bubbles to 0.05 MPa (G). In-mold molding was performed in the same manner as in Example 1, except that the expanded particles were used instead of the expanded particles used in Example 1, to obtain an expanded particle molded body. The measurement results of the physical properties of the obtained expanded particle molded body are shown in Table 1.
[0294] Embodiment 17
[0295] Expanded beads and expanded bead molded articles were obtained in the same manner as in Example 16 except that the ultraviolet absorbers shown in Table 1 were added in the amounts shown in Table 1. Table 1 shows the results of measurement of physical properties of the obtained expanded beads and expanded bead molded articles.
[0296] Comparative Example 1
[0297] Except that no hindered amine compound was used, expanded beads and expanded bead molded articles were obtained in the same manner as in Example 1. The measurement results of the physical properties of the obtained expanded beads and expanded bead molded articles are shown in Table 2. In addition, the obtained expanded bead molded articles were irradiated with light for 1980 hours (equivalent to 3 years of sunlight), resulting in the sample disintegrating and making it impossible to measure and evaluate.
[0298] Comparative Examples 10 to 14
[0299] [Manufacturing of expanded particles]
[0300] The resin shown in Table 2, the hindered amine compound shown in Table 2, zinc borate as a cell regulator, and a masterbatch containing carbon black (ethylene-propylene rubber (ethylene component 60 weight%): carbon black = 60:40) were supplied to the extruder and melt-kneaded to form a resin melt. In addition, each additive was supplied so that the content of zinc borate in the expanded particles was 500 mass ppm, the content of carbon black as an inorganic pigment in the expanded particles was 3 mass%, and the content of the hindered amine compound in the expanded particles was the content shown in Table 2.
[0301] The obtained resin melt was extruded from a strand forming die into a strand, and the extruded strand was water-cooled and then cut with a pelletizer to obtain cylindrical resin particles each having an average mass of 1 mg.
[0302] 500 g of the resin particles, 3.5 L of water as a dispersion medium, 3 g of kaolin as a dispersant, 0.2 g of sodium dodecylbenzenesulfonate (trade name "Neogen", manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) as a surfactant, 0.05 g of aluminum sulfate as a dispersing aid, and 5 g of bis(4-tert-butylcyclohexyl)peroxydicarbonate as an organic peroxide were placed in a 5 L pressure vessel. Next, carbon dioxide as a foaming agent was pressed into the pressure vessel, pressurized to a gauge pressure of 2.5 MPa (G), and the contents of the pressure vessel were stirred while heating to a foaming temperature (167°C) at a heating rate of 2°C / min. The temperature was then maintained for 15 minutes. Then, the contents of the pressure vessel were released to atmospheric pressure to obtain foamed particles. The obtained foamed particles were washed with water and placed in a centrifuge, and then left to mature at an atmospheric pressure of 23°C for 48 hours. The measurement results of the physical properties of the obtained foamed particles are shown in Table 2. The “vapor pressure range” in Table 2 refers to a range of vapor pressures in which the expanded beads have excellent in-mold moldability and a qualified product can be obtained based on the above-mentioned evaluation method.
[0303] In Comparative Examples 10 to 14, good in-mold molded products could not be obtained under the low molding pressure conditions (specifically, the conditions where the steam pressure was 0.32 MPa (G) or less).
[0304] Furthermore, in Comparative Examples 10 to 14 using polypropylene-based resins having a high degree of crystallinity, the vapor pressure range of the expanded particles was the same regardless of the type of hindered amine compound added.
[0305] [Manufacturing of Expanded Bead Molded Article]
[0306] An expanded bead molded article was obtained in the same manner as in Example 1. Table 2 shows the measurement results of the physical properties and the like of the obtained expanded bead molded article.
[0307] [Table 1]
[0308]
[0309] [Table 2]
[0310]
[0311] As can be seen from the results shown in Tables 1 and 2, the expanded particles of the embodiment have excellent in-mold formability even under low molding pressure conditions, and can manufacture good expanded particle molded bodies within a wider molding pressure range. In addition, it can be seen that the expanded particle molded bodies of the embodiment have excellent tensile properties such as tensile elongation and tensile strength in the tensile test. Further, it can be seen that the expanded particle molded bodies of the embodiment maintain tensile properties even in a weathering test under conditions equivalent to irradiation with sunlight for about 3 years, and the appearance does not change. It can be seen from this that the expanded particles of the present invention can produce expanded particle molded bodies with excellent long-term weathering resistance and excellent tensile properties, and the expanded particle molded bodies of the present invention have excellent long-term weathering resistance and excellent tensile properties.
[0312] Industrial Applicability
[0313] The foamed bead molded article of the present invention has excellent long-term weather resistance and excellent tensile properties. Therefore, the foamed bead molded article of the present invention can be appropriately used as impact absorbing materials, heat insulating materials, various packaging materials, etc., for food transport containers, packaging and cushioning materials for electrical and electronic components, vehicle parts such as automobile bumpers, building parts such as residential heat insulating materials, sundries, furniture, sporting goods, etc.
Claims
1. A foamed particle, characterized in that: The invention relates to foamed particles which use a polypropylene resin as a base resin and contain a hindered amine compound, wherein the polypropylene resin has a crystallinity of 45% or less, the hindered amine compound has a structure represented by the following formula (I), and the content of the hindered amine compound in the foamed particles is 0.01% by mass or more and 4% by mass or less, [Chemistry 1] In formula (I), X represents an alkylene group, and Y1 and Y2 each independently represent a hydrocarbon group or a hydrocarbon group bonded via an oxygen atom.
2. The expanded particles according to claim 1, wherein The invention further comprises an inorganic pigment, and the ratio of the content of the hindered amine compound to the content of the inorganic pigment is 0.01 to 8.
3. The expanded particles according to claim 1 or 2, characterized in that: The foamed particles further include an ultraviolet absorber A having a molecular weight of 360 or more, wherein the content of the ultraviolet absorber A in the foamed particles is 0.01 mass % or more and 2 mass % or less.
4. The expanded particles according to any one of claims 1 to 3, characterized in that The molecular weight of the hindered amine compound is 500 or more and 1000 or less.
5. The expanded particles according to any one of claims 1 to 4, characterized in that The bulk density of the foamed particles is 10 kg / m 3 Above 500kg / m 3 the following.
6. The expanded particles according to any one of claims 1 to 5, characterized in that The average cell diameter of the expanded particles is 50 μm or more and 250 μm or less.
7. A foamed particle molded body, characterized in that: A foamed bead molded article obtained by in-mold molding the foamed beads according to any one of claims 1 to 6.
Citation Information
Patent Citations
JP1971038359B1
JP1976022951B2
In-mold molding methof for polypropylene series resin foamed particle
JP1992046217B2
In-mold molding method for foamed polypropylene resin particles
JP1994022919B2
Manufacturing method of polypropylene-based resin pre-expanded particle molding
JP1994049795B2